Translations of Sovietisms: A Comparative Case Study of English Translations of Bulgakov’s The Master and Margarita - Kaloh Vid, Natalia (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
Bulgakov’s novel The Master and Margarita (1966-1967), a highly complex and multi-levelled narrative, is a challenge for any translator. Because Bulgakov’s narrative has been translated into English seven times (twice by the same translator, Glenny), with the first two translations published in the same year, 1967, and the latest in 2008, the novel offers a unique insight into the analysis of translation shifts, not merely from a synchronic, but also from a diachronic perspective. The emphasis here is on the translation of historical realia, referred to as Sovietisms, and pertaining to items characteristic of Soviet discourse of the 1930s, word-formations of the non-standard “Soviet Russian.” Bulgakov’s language is sated with Soviet vocabulary which refers to various cultural and socio-political elements of Soviet reality. Sovietisms occur at various levels (lexical, syntactical, stylistic and rhetorical) and should be carefully translated as a significant characteristic of Bulgakov’s style. A complete domestication of Sovietisms may lead to a loss of a connotative meaning essential for understanding the context, while a foreignization of these terms which are most likely unknown to Western readers may disturb the fluency of reading. The purpose of the analysis, thus, is to illustrate the use of domesticating/foreignizing strategies employed by the translators and to assess the translation choices, considering that the target audience of English-speaking readers are most likely completely unfamiliar with most terms. The analysis employs theory on foreignizing and domesticating principles, as well as taxonomies suggested by Vinay and Darbelnet (1958/1989), Vlakhov and Florin (1980) and Aixelá (1996) as the grounds for the case study.